Developing a secure base in family intervention: using the adult attachment projective system to assess attachment in family relationships - George, Carol; Wargo Aikins, Julie (Frontiers in Psychology, 2023)
Families are core to human well-being. Therapeutic intervention may be needed in the context of family disruptions. Attachment theory conceptualizes parents as the secure base and safe haven that support children's optimal development. Parents who have experienced their own attachment difficulties or traumas may not provide quality caregiving necessary for balanced secure parent-child attachment relationships. Following Bowlby's original thinking (1988), an attachment approach to family intervention views the therapist as a secure base that enables families to explore individual and system problems to restore equilibrium. Attachment informed therapy uses attachment theory to understand family functioning. However, the unavailability of valid economical assessment for examining attachment representations has constricted the practical utility of attachment theory in family therapy beyond applications of general concepts. This chapter describes the Adult Attachment Projective Pictures System (AAP) and explores its use as an efficient manner for assessing attachment representations within families that allows therapists to understand problematic interactions, disabling defensive processes, make predictions concerning negative patterns, and create targets for change and restorative intervention. Consolidating three decades of attachment and caregiving system research, we describe how distinct patterns of AAP responses for each adult attachment group map onto expected parenting and family system expectations and behaviors to provide a concise and informative framework. In addition to the traditional adult attachment patterns (Secure, Dismissing, Preoccupied, Unresolved), we describe for the first time expectations for two additional forms of incomplete pathological mourning (Failed Mourning and Preoccupied with Personal Suffering) that have been overlooked in the field.